Формування професійної компетентності майбутніх фахівців сфери зв’язку як педагогічна проблема - Сиверин, Юлія (Видавництво Львівської політехніки, 2012)
Исследуется проблема формирования профессиональной компетентности специалистов в области связи: уточняется категориальный аппарат, представлена структура профессиональной компетентности, выявлены педагогические условия и факторы, влияющие на формирование профессиональной компетентности. The article researches the problem of professional competence formation of communication sphere specialists. The author specifies categorical apparatus, shows the structure of professional competence, and reveals pedagogical conditions and factors effecting the formation of professional competence.
Формирование профессиональной компетентности будущих специалистов отрасли связи как педагогическая проблема
Formation of professional competence of future communication sphere specialists as a pedagogical problem
Keywords: профессиональная компетентность; профессиональная подготовка; специалист отрасли связи; структура профессиональной компетентности; professional competence; professional training; communication sphere specialist; structure of professional competence